A Mechanical Analysis of Polydicyclopentadiene with Metal Inserts Through Flexural Load - André Camboa (2013)
Polydicyclopentadiene (PDCPD) is being used in several products with particular success regarding to weight reduction and surface finish improvement. Despite the enough good mechanical properties presented by this thermosetting polymer, it needs to be adequately reinforced in applications requiring extra structural stability. This work studies the improvement of mechanical properties that may be achieved in PDCPD components reinforced with over-moulded steel wires by using the reaction injection moulding (RIM). Specimens, with and without metal inserts, were produced by using a special dedicated developed prototype RIM mould to be submitted to three point bending test, according to EN ISO 178:2003 standard. This paper presents and discusses the results obtained from the flexural tests, which allow concluding that the solution could be industrially used in feasible and advantageous conditions.